High-resolution carbon isotope chemostratigraphy of the upper Cambrian from the East Tarim Basin and implications for global correlation and paleoenvironment reconstruction - Xiao-Jun Zuo; Bo Chen; Hong-Xing Wei; Zhi-Xin Sun; Xin-Sheng Luo; Guo-Xiang Li; Zhi-Bin Huang; Miao Lu; Yong-Quan Chen; Ai-Hua Yang; Fang-Chen Zhao; Mao-Yan Zhu (Palaeoworld, 2026)

Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

A novel mechanical model for soil-pipe-roof interaction and multi-objective parameter optimization - Bo. Lu; Wen. Zhao; Pengjiao. Jia; Benzhe Ding; Haoran Liu; Quan Li (Computers and Geotechnics, 2026)

Visibly transparent photoluminescent film for energy-efficient chromatic glazing - Yingxiao Li; Quan Gong; Jihong Pu; Lin Lu (Chemical Engineering Journal, 2026)

Nutritional and metabolite composition characteristics of acid whey retentates obtained by membrane separation - Yanan Xia; Lu Li; Qing Wen; Quan Shuang; Lishan Sun; Musu Zha; Yongfu Chen (Food Chemistry, 2026)

Biomimetic hierarchical scaffold with Zn2+/Mg2+ dual-ion synergistic release for sequential immunomodulation to enhance bone regeneration - Dali Xu; Xin Liu; Jin Li; Jiaxin Quan; Boyang Zhang; Jiawei Zhang; Bowen Zhang; Sihan Lu; W. David Jamieson; Oliver K. Castell; Christopher P. Thomas; Ke Yang; et al. (Chemical Engineering Journal, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Reconstruction of vegetation and climate variability on the southeastern Tibetan plateau margin over the last 2000 years - Bing Song; Deke Xu; Limi Mao; Rong Wang; Qian Wang; Mingying Quan; Jingjing Li; Zhenyu Ni; Yanjie Zhao; Hao Li; Houyuan Lu; Xiangdong Yang (CATENA, 2026)

Early Fibroblast Remodeling Associated with Lung Tissue Preservation After FLASH Irradiation - Caihui Li; Luhao Tan; Qixiang Liu; Zhihui Li; Menghua Li; Xuefeng Yang; Guofu Dong; Cheng Quan; Jie Ping; Changzhen Wang; Hao Lu (Phenomics, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Decoupling functional group effects on uranium adsorption in UiO-66 through density functional theory and neural network modeling - Qufei Hu; Qing Wang; Haixia Quan; Lu Liu; Meifeng Li; Yonggang Lv (Journal of Hazardous Materials, 2026)

Spatial structure-mediated attenuation of protective LAB–pathogen competition: Quantitative modeling in structured versus liquid matrices - Chun-lei Lu; Jiao Li; Hua-xiang Li; Zhen-quan Yang (International Journal of Food Microbiology, 2026)

Hot air drying on wheat in the intelligence era: research advances, challenges, and future trends - Jiao Qingqing; Quan Xinge; Song Zhanhua; Lu Yao; Liu Mochen; Wang Jing; Cui Chengpeng; Wang Tiexin; Xiangyu Guan; Li Fade; Shaojin Wang; Yinfa Yan (Critical Reviews in Food Science and Nutrition, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Oligomeric versus monomeric procyanidins from Aganosma cymosa alleviate colitis via distinct gut microbiota-SCFAs-ferroptosis axes: a multi-omics study - Mengjiao Wang; Lu Bai; Haoyu Li; Yufei Hou; Quan Guo; Chi-Tang Ho; Sen Guo; Naisheng Bai (Food Bioscience, 2026)

Impact of emission inventory uncertainty on secondary inorganic aerosol simulation over Beijing–Tianjin–Hebei region - Yulong Li; Xiao Tang; Keyi Chen; Lei Kong; Wei Feng; Tianming Lu; Kai Cao; Quan Zhang; Zifa Wang (Atmospheric Pollution Research, 2026)

Synergistic role of microbial osmoregulation and electron transfer on enhancing high-salinity battery discharge wastewater treatment under electrochemical stimulation - Yongsen Shi; Zhinan Zheng; Yanyan Jia; Lan Tang; Haoting Quan; Kewen Li; Tianwei Hao; Lianpeng Sun; Hui Lu (Water Research, 2026)

A dual-benefit strategy for heavy rare earth element remediation and biomass valorization using Euglena gracilis: Insights into carbon flux redirection induced by lutetium (Lu³⁺) - Xin Wang; Feimiao Lu; Liyin Chen; Jun Jin; Pengcheng Feng; Xin Quan; Yanzhao Li; Jie Zhang; Mingcan Wu (Journal of Environmental Chemical Engineering, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Toxoplasma GRA72 is Involved in Membrane-Associated Functions and Metabolic Homeostasis Revealed by Transcriptomic Analysis - Xin-Sheng Lu; Xing Tian; Jing Li; Chen-Ran Tian; Xing-Quan Zhu; Xiao-Nan Zheng (Acta Parasitologica, 2026)

Nonstationary agricultural drought risk under compound meteorological drought and hot conditions - Quan Zhang; Ziyang Lu; Jiaolong Ying; Yue Qiu; Panpan Wang; Zhipeng Xu; Dongxiao Xu; Yongping Li (Journal of Hydrology, 2026)

Laser direct construction of multiple bioinspired kirigami with enhanced fog harvesting - Xiaojie Li; Weiru Xu; Guangwen Zhang; Junjie Lu; Longzhe Quan (Chemical Engineering Journal, 2026)

Gender-specific association between PM2.5 exposure and cognitive function in middle-aged and elderly chinese: Evidence from CHARLS - Man Quan; Jing Cui; Yukui Chen; Jiayi Hao; Chenshu Ge; Xiaomei Li; Juan Wang; Duolao Wang; Leilei Pei; Yijun Kang; Lu Ye (Air Quality, Atmosphere & Health, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Oceanic deoxygenation linked to enhanced water column stratification in the eastern Tethys during Cretaceous Oceanic Anoxic Event 2 - Yu Liang; Yong-Xiang Li; Hongxuan Lu; Huanye Wang; Cece Wang; Cheng Quan; Weiguo Liu; Mei-Fu Zhou; Zhonghui Liu (Global and Planetary Change, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Associations of prenatal per- and polyfluoroalkyl substances exposure with glucose homeostasis and gestational diabetes mellitus: A systematic review and meta-analysis - Feng Quan; Chuanzi Gao; Jason T. Magnuson; Yu Li; Wenhui Qiu; Rongrong Xuan; Haiyan Lu; Yi Zheng (Journal of Hazardous Materials, 2026)

Identification of the geographical origin of wild rice field eel (Monopterus albus) in China by stable isotopes - Weiwei Lv; Muyan Li; Yangyang Lu; Yifan Zhao; Weiwei Huang; Hang Yang; Quan Yuan; Yuning Zhang; Mingyou Li; Wei Hu; Chunxia Yao; Danhe Wang; et al. (Food Control, 2026)

Effect of freeze-thaw cycles on nitrogen retention in an alpine topsoil amended with peanut shell hydrochar - Yuxi Wu; Jiawen Zhang; Yadi Ai; Weici Quan; Yiwei Gong; Kaiming Yang; Jin Gao; Lu Li; Caiwei Hao; Wenbo Li; Wenjie Ai; Kai Yang; et al. (Environmental Research, 2026)

Mechanisms of bioelectrochemistry enhanced saline aerobic granular sludge: From EPS monomers to microbial metabolism - Aqiang Ding; Shikang Li; Wenkai Yao; Yuhao Tong; Lin Quan; Chun Yang; Fuzhong Song; Daijun Zhang; Peili Lu (Chemical Engineering Journal, 2026)

Complement C3a Suppresses Spinal Cord Neural Stem Cell Activation by Inhibiting UCHL1 via the NF-κB p65/Nrf2 Pathway - Lu Ding; Xinyue Li; YaQin Guo; Feng-Quan Zhou; David Y. B. Deng (Neuroscience Bulletin, 2026)
Activation of spinal cord neural stem cells (NSCs) and subsequent neurogenesis holds a promising alternative for spinal cord injury (SCI) repair. Our previous study demonstrated that complement C3a, derived from reactive astrocytes, inhibits NSC proliferation by suppressing protein aggregate clearance through the deubiquitinating enzyme ubiquitin carboxy-terminal hydrolase L1 (UCHL1)-proteasome system post-SCI. However, the potential molecular mechanism by which C3a modulates NSC activation via this pathway remains unclear. Here, we revealed that C3a/C3a receptor (C3aR) signaling activated NF-κB p65, which in turn inhibited Nrf2 activity and UCHL1 expression, resulting in diminished proteasome activity and the accumulation of protein aggregates, and ultimately impaired NSC activation. Both knockdown of NF-κB p65 and Nrf2 upregulation restored UCHL1 expression and proteasome activity in vitro , promoting NSC activation by enhancing protein aggregate clearance. Mechanistically, we found that NF-κB p65 regulated Nrf2 activity through a dual mechanism: (1) promoting Keap1-dependent ubiquitination and proteasome degradation of Nrf2; (2) inhibiting protein kinase C-mediated Nrf2 phosphorylation and nuclear translocation. Using the dual-luciferase reporter assay and chromatin immunoprecipitation (ChIP) analysis, we further identified UCHL1 as a direct transcriptional target of Nrf2. Importantly, in vivo experiments using SCI mice confirmed that either C3aR blockade, NF-κB p65 knockdown, or Nrf2 overexpression could rescue SCI-induced UCHL1 downregulation. Together, this study uncovers the C3a-NF-κB p65-Nrf2-UCHL1-proteasome axis as a critical regulator of NSC activation after SCI. This may provide novel molecular targets and intervention strategies for SCI repair.

In-situ mineral carbonation of ultramafic tailings for carbon dioxide removal: A critical review - Xiangyang Lu; Liang Xu; Xiaochun Li; Yunlu Hou; Quan Chen; Qi Li (Process Safety and Environmental Protection, 2025)

Pressure relief and zonal extraction and utilization of medium-thick coal seams with high gas content - Zechen Chang; Pengxiang Zhao; Shugang Li; Diego Maria Barbieri; Xu Guo; Weidong Lu; Quan Jin; Linyue Jie (Geomechanics for Energy and the Environment, 2025)

Environmental hazard profile of gadolinium (Gd3+): Mechanistic insights into its ecotoxicity towards Euglena gracilis from a multi-level investigation - Xin Wang; Feimiao Lu; Guimei Wu; Jun Jin; Yanzhao Li; Jie Zhang; Xin Quan; Mingcan Wu; Xingwei Cai; Zhiyuan Liu (Environmental Research, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Design and performance analysis of an electric threshing drum and its speed control system for combine harvester - Zhihao Zhu; Xiaoyu Chai; Lizhang Xu; Li Quan; Chaochun Yuan; En Lu; Shuofeng Weng (Biosystems Engineering, 2025)

Community and functional succession of corrosive microorganisms during flowback and produced water management in Sichuan Basin - Jiayi Qing; Aqiang Ding; Zhengming Hou; Lin Quan; Yuhao Tong; Junou Pan; Xiong Li; Peili Lu (Journal of Water Process Engineering, 2025)

Simultaneous detection of multispecies foodborne pathogens using multiple phage-functionalized nanozyme - Mengyuan Tan; Xin Li; Lu Gao; Qin Hu; Zhen-quan Yang; Xuechao Xu (Journal of Hazardous Materials, 2025)

PFAS in bottled water from China: High prevalence of ultrashort-chain compounds, health risks, and global insights - Haoting Quan; Fahui Ji; Zhen Zhong; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Comparative study of thermodynamic and material planetary boundary layer height in Beijing during the heatwaves - Lindong Dai; Yongnan Zhang; Yongjing Ma; Simin Yang; Zengshou Liu; Pengkun Ma; Yubing Pan; Zhiheng Liao; Shao Xiao; Yunjie Xia; Li Lu; Danjie Jia; et al. (Advances in Space Research, 2025)

Enhanced performance of algal-bacterial granular sludge in treating wastewater under PFOA stress: Synergistic effects and mechanisms - Fahui Ji; Xiaojing Yang; Haoting Quan; Jinxia Liu; Rui Li; Hui Lu (Journal of Hazardous Materials, 2025)

Unveiling the role of N-doped carbon quantum dots in relieving humic acid inhibition and promoting methanogenesis via enhanced electron transfer - Qiang Liu; Mahmoud Mazarji; Yeqing Li; Lu Feng; Hongjun Zhou; Quan Xu; Alastair James Ward; Yajing Wang; Jianping Su; Chunming Xu; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Effects of nano-selenium on the histopathological changes and gene expression of rainbow trout (Oncorhynchus mykiss) spleen under heat stress - Junhao Lu; Zhe Liu; Jiahui Zhang; Lanlan Li; Guiyan Zhao; Yucai Pan; Jinqiang Quan; Guolin Song (Fish Physiology and Biochemistry, 2025)

Estimating evapotranspiration from deciduous broadleaf forests by considering the effect of foliar litter - Chenhao Fu; Shujing Qin; Lei Cheng; Lingcheng Li; Quan Zhang; Xuxin Lei; Pan Liu; Lu Zhang (Agricultural and Forest Meteorology, 2025)

Pyrolysis of three typical halophytes and their blends from coastal saline-alkali lands: Pyrolysis behaviors, kinetics and thermodynamics - Zhuangzhuang Liu; Qi Li; Mingyun Jia; Shipeng Lu; Dongqin Zhou; Zhaoqi Hou; Quan Zhou; Lei Liu; Jinping Yu (Journal of Environmental Management, 2025)

Ultrafine bismuth nanoclusters for highly efficient electrochemical CO2 reduction to formate - Fangqi Yang; Pengfei Li; Haoming Yu; Xu Han; Tonglin Yang; Quan Zhang; Jiong Lu; Jie Zhang (Chemical Engineering Journal, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Microbial community structure and functional characteristics in shale gas flowback water from marine shale formation in Sichuan Basin, China: Insights into C-N-P-S cycle and correlations - Lin Quan; Aqiang Ding; Jun Liu; Yuhao Tong; Jiayi Qing; Junou Pan; Xiong Li; Bin Lei; Daijun Zhang; Peili Lu (Journal of Water Process Engineering, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

Investigating the fine structures of ginkgo starch during kernel development and their correlations with thermal properties - Yan Lu; Lian Zhou; Cai-Yun Zhang; Yan Qi; Xiao-Min Zhang; Zhang Pan; Hong-Jia Zhang; Yu-Ping Ling; Qing Liu; Chang-Quan Zhang; Li Wang (Food Chemistry, 2025)

Efficient visual detection of sodium nitrite based on redox-responsive photonic crystal sensors - Juan Wei; Jingjing Xu; Chuyi Wang; Ya-Fei Yang; Yue Zhang; Runyan Ni; Yong-Quan Xu; Dejian Huang; Lu Li (Chemical Engineering Journal, 2025)

Fate of myofibrillar protein-bound Nε-(carboxymethyl)lysine in the presence of the human colonic microbiota after gastrointestinal digestion - Shuqi Hao; Zeyu Lu; Mengyu Ye; Na Li; Jiayi Hu; Wei Quan; Jiwen Cheng; Huaide Xu; Mei Li (Food Bioscience, 2025)

Multi-omics combined with physiological and biochemical analyses provide new insights into the molecular mechanisms of nano‑selenium on rainbow trout head kidney against heat stress - Junhao Lu; Zhe Liu; Jinqiang Quan; Jiahui Zhang; Guiyan Zhao; Lanlan Li; Yucai Pan (Aquaculture, 2025)

Encapsulation of Lacticaseibacillus rhamnosus and Staphylococcus xylosus using sodium alginate improves flavour and the nutritional value of pork broth - Chun-lei Lu; Hua-xiang Li; Fedrick C. Mgomi; Zhen-quan Yang (Food Bioscience, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Genome-wide association study reveals genetic loci for seed density per silique in rapeseed (Brassica napus L.) - Youjuan Quan; Haidong Liu; Kaixiang Li; Liang Xu; Zhigang Zhao; Lu Xiao; Yanmei Yao; Dezhi Du (Theoretical and Applied Genetics, 2025)

Effects of nitrification inhibitor and maize straw application on N2O and N2 emissions from two agricultural soils: A 15N tracer study - Xinghan Zhao; Zhi Quan; Geshere Abdisa Gurmesa; Bin Huang; Haoming Yu; Feifei Zhu; Zhifeng Xun; Chang Liu; Dong Liu; Xiusen Yang; Jie Li; Yunting Fang; et al. (Soil Ecology Letters, 2025)

Efficient weed segmentation in maize fields: A semi-supervised approach for precision weed management with reduced annotation overhead - Zhiming Guo; Yi Xue; Chuan Wang; Yuhang Geng; Ruoyu Lu; Hailong Li; Deng Sun; Zhaoxia Lou; Tianbao Chen; Jianzhe Shi; Longzhe Quan (Computers and Electronics in Agriculture, 2025)

Unveiling shape-dependent intrinsic activity of cadmium sulfide (CdS) for photocatalytic uranium(VI) reduction - Yihao Quan; Sen Lu; Qingliang Wang; Hongqiang Wang; Eming Hu; Xinnan Wang; Jiacheng Bao; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

Green hydrogen and porous carbon materials co-harvested through CO2-steam co-mediated gasification - Xin Zhang; Chuan Qin; Yi Lu; Quan Liu; Hongkang Liu; Chun Wang; Guanyu Zhang; Ge Kong; Kejie Wang; Jing Li; Jianying Shang; Xuesong Zhang; et al. (Bioresource Technology, 2025)

Effects of olanzapine in the improvement of body weight and appetite in patients with cancer or receiving chemotherapy: a systematic review and meta-analysis - Lu Yuan; Xin-Yu Li; Lu Xu; Si-Jie Quan; Yan-Bing Huang; Hui Zheng (European Journal of Clinical Pharmacology, 2025)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Polystyrene microplastics facilitate the chemical journey of phthalates through vegetable and aggravate phytotoxicity - Bogui Pan; Boyou Pan; Yiyuan Lu; Kunzheng Cai; Xiaoqiong Zhu; Li Huang; Lei Xiang; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Enhancement of livestock wastewater treatment by a novel wooden-modified biocarrier - Zhiwei Li; Quan Feng; Mingyi Lu; Fan Qin; Zongzheng Liu; Rongbo Guo (Environmental Pollution, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Effects of a novel sawdust-modified carrier on performance, bioaccumulation and microbial community of sequencing batch reactor - Zhiwei Li; Quan Feng; Mingyi Lu; Fengyuan Zhang; Rongbo Guo (Journal of Environmental Management, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Iron driven organic carbon capture, pretreatment, recovery and upgrade in wastewater: Process technologies, mechanisms, and implications - Quan Liao; Lianpeng Sun; Hui Lu; Xianglin Qin; Junhong Liu; Xinzhe Zhu; Xiao-yan Li; Lin Lin; Ruo-hong Li (Water Research, 2024)

Differential impacts of microplastics on carbon and nitrogen cycling in plant-soil systems: A meta-analysis - Yige Liu; Siyi Chen; Pengyu Zhou; Haochen Li; Quan Wan; Ying Lu; Bo Li (Science of The Total Environment, 2024)

Trifolium repens L. recruits root-associated Microbacterium species to adapt to heavy metal stress in an abandoned Pb-Zn mining area - Xin-qi Yuan; Yi-yi Liu; Si-chen Wang; Ya-qi Lu; Yin-jie Li; Jin-quan Chen; Chang-qun Duan (Science of The Total Environment, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

A biguanide chitosan-based hydrogel adhesive accelerates the healing of bacterial-infected wounds - Junhao Shi; Xin Hao; Hanyu Yang; Zhimin He; Jiaju Lu; Yunhui Li; Liang Luan; Quan Zhang (Carbohydrate Polymers, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Comparison of intestinal absorption of soybean protein isolate-, glutenin- and peanut protein isolate-bound Nε-(carboxymethyl) lysine after in vitro gastrointestinal digestion - Shuqi Hao; Mengyu Ye; Na Li; Zeyu Lu; Wei Quan; Huaide Xu; Mei Li (Food Research International, 2024)

Kinetically accelerated lithium storage in (LiFeCoNiMnCr)2O3 enabled by hollow multishelled structure, oxygen vacancies and high entropy engineering - Fengfeng Dong; Rui Wang; Yao Lu; Haoyu Xu; Quan Zong; Lijing Yan; Xianhe Meng; Tingli Ma; Dongyun Li; Qingyi Lu; Lizong Dai; Qiaoling Kang (Chemical Engineering Journal, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

Solar-driven adaptive radiative cooling coating with polymer carbon dots-enhanced photoluminescence for urban skin - Quan Gong; Ho Chun Wong; Jianheng Chen; Pei Li; Lin Lu (Chemical Engineering Journal, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

CdS@NiCr-LDH Z-scheme heterojunction with high adsorption–photocatalysis for uranium(VI) removal without any sacrificial agent - Sen Lu; Yuqiang Yin; Jiacheng Bao; Hongqiang Wang; Zhiwu Lei; Eming Hu; Qi Xin; Yihao Quan; Jianming Li; Qingliang Wang (Journal of Environmental Chemical Engineering, 2024)

A cleaner-sustainable process for recovering valuable elements from steel slag with acetic acid: Leaching studies and multi-value-added products - Mingyuan Yang; Shuo Zhang; Yelei Wang; Zilong Li; Juan Wen; Xuejun Quan; Cunfang Lu (Journal of Environmental Chemical Engineering, 2024)

A reusable, healable, and biocompatible PEDOT:PSS hydrogel-based electrical bioadhesive interface for high-resolution electromyography monitoring and time–frequency analysis - Rongtai Wan; Jiawen Yu; Ziyi Quan; Hude Ma; Jinhao Li; Fajuan Tian; Wen Wang; Yajuan Sun; Junyan Liu; Dian Gao; Jingkun Xu; Baoyang Lu (Chemical Engineering Journal, 2024)

Characterization of the complete mitochondrial genome of Ergasilus anchoratus Markevich, 1946 (Ergasilidae) and phylogeny of Copepoda - Cong-jie Hua; Yan Huang; Hui-quan Li; Jin-mei Feng; Jia-lu Qiao; Song Hu; Wei Liu; Xi-ji Shu (Systematic Parasitology, 2024)

Interfacial OOH* mediated Fe(II) regeneration on the single atom Co-N-C catalyst for efficient Fenton-like processes - Bao-Gang Fu; Xiangtong Zhou; Yilin Lu; Wen-Zhu Quan; Chunmei Li; Liang Cheng; Xiang Xiao; Yang-Yang Yu (Journal of Hazardous Materials, 2024)

Does creation-oriented culture promote ESG activities? Evidence from the Chinese market - Quan Wen; Shipian Shao; Yaopeng Wang; Jingke Hong; Ke Lu; Qingyue Zhao; Heran Zheng; Li Ma (Global Environmental Change, 2024)

High entropy engineering construction of high active and stable hybrid structure cathodes for advanced ceramic membrane fuel cells - Xiaoyong Lu; Quan Yang; Ruoyu Li; Shiyue Zhu; Jianjian Zhang; Daofu Liu; Dong Tian; Yanzhi Ding; Yihan Ling (Fuel, 2024)

Polyoxometalate-derived bi-functional crystalline/amorphous interfaces with optimized d-electron configuration for efficient self-powered hydrazine-seawater splitting - Qinghao Quan; Xiaolei Li; Chen Song; Qisen Jia; Huasen Lu; Xuejing Cui; Guangbo Liu; Xin Chen; Luhua Jiang (Chemical Engineering Journal, 2024)

Augmenting bamboo strength and thermal stability for sustainable construction - Jin Qian; Kong Yue; Shaodong Liu; Dong Lu; Peng Wu; Quan Li (Journal of Cleaner Production, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

Simultaneous denitrification enhancement and sludge reduction based on novel suspended carrier modified using activated carbon and magnetite at low carbon/nitrogen ratio - Zhiwei Li; Quan Feng; Fengyuan Zhang; Feng Zhao; Mingyi Lu; Fan Qin; Rongbo Guo (Bioresource Technology, 2024)

Nitric oxide and ion channels mediate l-cysteine-induced inhibition of colonic smooth muscle contraction - Xiaojing Quan; Min Zhang; Zhaojun Qiao; Xuan Kou; Qiong Xue; Jinhai Wang; Lu Li (Journal of Muscle Research and Cell Motility, 2024)

Coexposure to Multiple Metals and the Risk of Abnormal Blood Pressure in Chinese Children - JingJing Quan; Li Chen; Hong Yuan; Yao Lu; Minxue Shen; Bin Yi; Xiang Chen; Zhijun Huang (Exposure and Health, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Large DNA fragment knock-in and sequential gene editing in Plasmodium falciparum: a preliminary study using suicide-rescue-based CRISPR/Cas9 system - Junnan Lu; Ying Tong; Rui Dong; Yijun Yang; Wen Hu; Minghong Zhang; Quan Liu; Siting Zhao; John H. Adams; Li Qin; Xiaoping Chen (Molecular and Cellular Biochemistry, 2024)

Effect of edible oil type on the formation of protein-bound Nε-(carboxymethyl)lysine in roasted pork patties - Na Li; Xuan Wu; Hailong Liu; Diandong Xie; Shuqi Hao; Zeyu Lu; Wei Quan; Jie Chen; Huaide Xu; Mei Li (Food Research International, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Nano-selenium Antagonizes Heat Stress-Induced Apoptosis of Rainbow Trout (Oncorhynchus mykiss) Hepatocytes by Activating the PI3K/AKT Pathway - Lanlan Li; Zhe Liu; Guiyan Zhao; Jinqiang Quan; Jun Sun; Junhao Lu (Biological Trace Element Research, 2023)

The alkaloids with neuroprotective effect from the root bark of Ailanthus altissima - Qing Shao; Tian-Yi Li; Wei Quan; Hui Wang; Ke-Yu Yan; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu (Natural Product Research, 2023)

Photocatalytic membrane coated with α-Fe2O3/Fe3O4 for enhanced filtration performance and antifouling property in surface water treatment - Yuanqing Guo; Quan Liu; Xiaobin Tang; Heng Liang; Guibai Li; Liwei Yang; Lu Wang; Xiaoling Li; Yan Sun (Chemosphere, 2023)

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

Rhizosphere effect on the relationship between dissolved organic matter and functional genes in contaminated soil - Qingqing Wang; Shiyang Wei; Yang Zhou; Ondřej Mašek; Muhammad Amjad Khan; Dong Li; Quan Liu; Yin Liu; Wenkang Lu; Xuesong Su; Zhiqiang Zhu; Xiaojun Zhao; et al. (Journal of Environmental Management, 2023)

A classification and identification model of extra virgin olive oil adulterated with other edible oils based on pigment compositions and support vector machine - Cong-Hui Lu; Bao-Qiong Li; Quan Jing; Dong Pei; Xin-Yi Huang (Food Chemistry, 2023)

Acteoside palliates d-galactose induced cognitive impairment by regulating intestinal homeostasis - Maiquan Li; Mingzhi Zhu; Wei Quan; Weisu Huang; Xia Liu; Can Zhang; Baiyi Lu; Xing Xiao; Zhonghua Liu (Food Chemistry, 2023)

Tree-inspired and scalable high thermal conductivity ethylene–vinyl acetate copolymer/expanded graphite/paraffin wax phase change composites for efficient thermal management - Xinpeng Hu; Xianrong Huang; Bingqing Quan; Chuanbiao Zhu; Youqiang Yang; Mengjie Sheng; Chao Ding; Haoye Wen; Xiaolong Li; Jingang Wei; Hao Wu; Xiang Lu; et al. (Chemical Engineering Journal, 2023)

Horizontal ecological compensation mechanism and green low-carbon development in river basins: evidence from Xin’an River basin - Tianshu Quan; Hui Zhang; Jing Li; Binqiang Lu (Environmental Science and Pollution Research, 2023)

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Clonal fragmentation drives performance deterioration of epiphytic and lithophytic ferns in a karst forest - Qian Dai; Yu-Xuan Mo; Quan Chen; Liang Song; Li-Min Zhang; Gbadamassi G.O. Dossa; Hua-Zheng Lu (Flora, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

Coexposure to multiple metals and renal tubular damage: a population-based cross-sectional study in China’s rural regions - JingJing Quan; Yan Li; Minxue Shen; Yao Lu; Hong Yuan; Bin Yi; Xiang Chen; Zhijun Huang (Environmental Science and Pollution Research, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Dietary nano-selenium alleviates heat stress-induced intestinal damage through affecting intestinal antioxidant capacity and microbiota in rainbow trout (Oncorhynchus mykiss) - Lanlan Li; Zhe Liu; Jinqiang Quan; Jun Sun; Junhao Lu; Guiyan Zhao (Fish & Shellfish Immunology, 2023)

All-climate outstanding-performances lithium-ion batteries enabled by in-situ constructed gel polymer electrolytes - Lijiao Quan; Qili Su; Haojun Wu; Weiyi Huang; Mingzhu Liu; Yong Lu; Zhe Li; Haijing Liu; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2023)

A novel method based on solid phase extraction and liquid chromatography-tandem mass spectrometry warrants occurrence of trace xanthates in water - Yu-Ting Qiao; Ying-Xin Lu; Peng-Fei Yu; Nai-Xian Feng; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Chemosphere, 2023)

Effect of Club cell secretory proteins on the association of tobacco smoke and PAH co-exposure with lung function decline: A longitudinal observation of Chinese coke oven workers - Lu Liu; Jiajun Wei; Yong Wang; Quan Feng; Shugang Guo; Gaisheng Liu; Jun Dong; Liuquan Jiang; Qiang Li; Jisheng Nie; Jin Yang (International Journal of Hygiene and Environmental Health, 2023)

Effect of multi-type oxides on the catalytic pyrolysis behaviors of 5-amino-1H-tetrazole - Jiu Chen; Quan Liu; Xian-Zhao Song; Si-Yuan Zhou; Bin Li; Li-Feng Xie; Guang-Cheng Yang; Cheng-Yan Cao; Song Lu; Dan Zhang (Fuel, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Idiomarina rhizosphaerae sp. nov. isolated from rhizosphere soil of Kalidium cuspidatum, and reclassification of Idiomarina andamanensis as Pseudidiomarina andamanensis comb. nov., and Idiomarina mangrovi as Pseudidiomarina mangrovi comb. nov - Lu-Fan Li; Lian Xu; Hua-Mei Wei; Ji-Quan Sun (Archives of Microbiology, 2022)

Novel SNPs in the 3′UTR Region of GHRb Gene Associated with Growth Traits in Striped Catfish (Pangasianodon hypophthalmus), a Valuable Aquaculture Species - Liang-Sen Jiang; Zhuo-Hao Ruan; Zhi-Qiang Lu; Yi-Fu Li; Yuan-Yuan Luo; Xi-Quan Zhang; Wen-Sheng Liu (Fishes, 2022)
The striped catfish, Pangasianodon hypophthalmus is an important freshwater aquaculture species in Southeast Asian countries due to its rapid growth. The growth hormone receptor (GHR) is a significant regulatory factor for the growth axis and has great potential applications in animal genetic breeding. This study aims to characterize the GHRb cDNA of the striped catfish and analyze the distribution of its mRNA. Screening of single nucleotide polymorphisms’ (SNPs) loci and diplotypes was performed to provide basic information for the assisted selection of molecular markers in genetic breeding. The results showed that the GHRb cDNA of striped catfish had 2791 bp, which encoded for 569 amino acids. In a phylogenyic study, the ghrb of the striped catfish was clustered with those of other catfish and they were highly homologous. Quantitative real-time PCR (qRT-PCR) experiments showed that GHRb mRNA was expressed in ten different organs of the striped catfish, with the highest expression level in the liver. Five SNP and a haplotype block were identified in the 3′UTR of the GHRb gene using the direct sequencing of 307 individuals. Three haplotypes were found and four diplotypes were constructed. The association analysis revealed that these polymorphisms were significantly associated with growth traits in the striped catfish (p

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Pruning improves seedling development and bioactive secondary metabolite accumulation in the leaves of Ginkgo biloba - Meng Cao; Quan Gan; Yuan Xu; Jin Kai Lu; Lei Zhong; Mingxian Wang; Sian Liu; Li Wang (Trees, 2022)

Dietary nanoselenium supplementation for heat-stressed rainbow trout: effects on organizational structure, lipid changes, and biochemical parameters as well as heat-shock-protein- and selenoprotein-related gene expression - Lanlan Li; Zhe Liu; Jinqiang Quan; Junhao Lu; Guiyan Zhao; Jun Sun (Fish Physiology and Biochemistry, 2022)

Functional diversity loss and change in nocturnal behavior of mammals under anthropogenic disturbance - Xueyou Li; Wenqiang Hu; William V. Bleisch; Quan Li; Hongjiao Wang; Wen Lu; Jun Sun; Fuyou Zhang; Bu Ti; Xuelong Jiang (Conservation Biology, 2022)
In the Anthropocene, understanding the impacts of anthropogenic influence on biodiversity and behavior of vulnerable wildlife communities is increasingly relevant to effective conservation. However, comparative studies aimed at disentangling the concurrent effect of different types of human disturbance on multifaceted biodiversity and on activity patterns of mammals are surprisingly rare. We applied a multiregion community model to separately estimate the effects of cumulative human modification (e.g., settlement, agriculture, and transportation) and human presence (aggregated presence of dogs, people, and livestock) on species richness and functional composition of medium‐ and large‐bodied mammals based on camera trap data collected across 45 subtropical montane forests. We divided the detected mammal species into three trophic guilds–carnivores, herbivores, and omnivores–and assessed the nocturnal shifts of each guild in response to anthropogenic activities. Overall, species richness tended to increase ( β coefficient = 0.954) as human modification increased but richness decreased as human presence increased ( β = –1.054). Human modification was associated with significantly lower functional diversity (mean nearest taxon distance [MNTD], β = –0.134; standardized effect sizes of MNTD, β = –0.397), community average body mass ( β = –0.240), and proportion of carnivores ( β = –0.580). Human presence was associated with a strongly reduced proportion of herbivores ( β = –0.522), whereas proportion of omnivores significantly increased as human presence ( β = 0.378) and habitat modification ( β = 0.419) increased. In terms of activity patterns, omnivores ( β = 12.103) and carnivores ( β = 9.368) became more nocturnal in response to human modification. Our results suggest that human modification and human presence have differing effects on mammals and demonstrate that anthropogenic disturbances can lead to drastic loss of functional diversity and result in a shift to nocturnal behavior of mammals. Conservation planning should consider concurrent effects of different types of human disturbance on species richness, functional diversity, and behavior of wildlife communities.

Identification of the soybean small auxin upregulated RNA (SAUR) gene family and specific haplotype for drought tolerance - Guang Li; Quan Wang; Lei Lu; Shoudong Wang; Xiao Chen; Muhammad Hafeez U. Khan; Yaohua Zhang; Suxin Yang (Biologia, 2022)

RNA-seq Analysis Reveals Alternative Splicing Under Heat Stress in Rainbow Trout (Oncorhynchus mykiss) - Jun Sun; Zhe Liu; Jinqiang Quan; Lanlan Li; Guiyan Zhao; Junhao Lu (Marine Biotechnology, 2022)

Synthesis, antiproliferative, and antimicrobial properties of novel phthalimide derivatives - Chun-Lan Chi; Lu Xu; Jun-Jie Li; Yang Liu; Bao-Quan Chen (Medicinal Chemistry Research, 2022)

Optimization of ultrasound and microwave-assisted extraction of sweet cherry tree branches and chemical component analysis by UPLC–MS/MS - Huimin Zhang; Hongguang Yan; Cuixiang Lu; Hui Lin; Quan Li (Trees, 2021)

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Synthesis and antitumor effects of a new class of 1,2,4-triazole derivatives - Zheng Wu; Xin Li; Chun-Lan Chi; Lu Xu; Yong-Yue Sun; Bao-Quan Chen (Medicinal Chemistry Research, 2021)

Poly(L-Glutamic Acid)-Based Brush Copolymers: Fabrication, Self-assembly, and Evaluation as Efficient Nanocarriers for Cationic Protein Drug Delivery - Xin Li; Chao Lu; Wenquan Xia; Guilan Quan; Ying Huang; Xuequn Bai; Feiyuan Yu; Qian Xu; Wanbing Qin; Daojun Liu; Xin Pan (AAPS PharmSciTech, 2020)

Design, synthesis, and antitumor evaluation of novel naphthalimide derivatives - Xin Li; Zheng Wu; Lu Xu; Chun-Lan Chi; Bao-Quan Chen (Medicinal Chemistry Research, 2020)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Performance of Post-Processed Methods in Hydrological Predictions Evaluated by Deterministic and Probabilistic Criteria - Xiang-Quan Li; Jie Chen; Chong-Yu Xu; Lu Li; Hua Chen (Water Resources Management, 2019)

Spatio-temporal remote sensing of vertical and seasonal chlorophyll- a:b ratio in Tamarix ramosissima - John Nyongesah Maina; Pingheng Li; Lu Xu; Quan Wang (International Journal of Remote Sensing, 2019)

Effects of glyphosate on soybean metabolism in strains bred for glyphosate-resistance - Wei-yu Li; Ping Lu; Hao Xie; Gui-quan Li; Jing-xuan Wang; Dong-yu Guo; Xing-yu Liang (Physiology and Molecular Biology of Plants, 2019)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

CLDN6 enhances chemoresistance to ADM via AF-6/ERKs pathway in TNBC cell line MDAMB231 - Minlan Yang; Yanru Li; Yang Ruan; Yan Lu; Dongjing Lin; Yinping Xie; Bing Dong; Qihua Dang; Chengshi Quan (Molecular and Cellular Biochemistry, 2018)

Fragmented particles containing octreotide acetate prepared by spray drying technique for dry powder inhalation - Ailin Hou; Lu Li; Ying Huang; Vikramjeet Singh; Chune Zhu; Xin Pan; Guilan Quan; Chuanbin Wu (Drug Delivery and Translational Research, 2018)

GbABR1 is associated with Verticillium wilt resistance in cotton - Yujia Liu; Xin Liu; Lu Long; Weina Wang; Quan Sun; Bo Li; Chenxiao Wang; Jieru Cheng; Yuanyuan Zhang; Yuanhui Xie; Lingling Xu; Runkuan Qin; et al. (Biologia, 2018)

Surface wave attenuation based polarization attributes in time-frequency domain for multicomponent seismic data - Xuan-Lin Kong; Hui Chen; Zhi-Quan Hu; Jia-Xing Kang; Tian-Ji Xu; Lu-Ming Li (Applied Geophysics, 2018)

An amplitude suppression method based on the decibel criterion - Xuan-Lin Kong; Hui Chen; Jin-Long Wang; Zhi-quan Hu; Dan Xu; Lu-Ming Li (Applied Geophysics, 2017)

Algorithm to improve accuracy of energy expended in a room calorimeter - Haiying Quan; Wenrui Hao; Lu Li; Ming Sun; Kuan Zhang (Medical & Biological Engineering & Computing, 2017)

Genome editing in Drosophila melanogaster: from basic genome engineering to the multipurpose CRISPR-Cas9 system - Xingjie Ren; Kristof Holsteens; Haiyi Li; Jin Sun; Yifan Zhang; Lu-Ping Liu; Qingfei Liu; Jian-Quan Ni (Science China Life Sciences, 2017)

Taxonomy and pathogenicity of Leptographium species associated with Ips subelongatus infestations of Larix spp. in northern China, including two new species - Xue-Wei Liu; Hui-Min Wang; Quan Lu; Cony Decock; Yong-Xia Li; Xing-Yao Zhang (Mycological Progress, 2017)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Antagonistic Streptomyces enhances defense-related responses in cotton for biocontrol of wilt caused by phytotoxin of Verticillium dahliae - Lei Xue; Mei-Ying Gu; Wan-Li Xu; Jian-Jun Lu; Quan-Hong Xue (Phytoparasitica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The application study on the multi-scales integrated prediction method to fractured reservoir description - Shuang-Quan Chen; Lian-Bo Zeng; Ping Huang; Shao-Han Sun; Wan-Lu Zhang; Xiang-Yang Li (Applied Geophysics, 2016)

Epidemiological situation and genetic analysis of H7N9 influenza viruses in Shanghai in 2013 - Fei-Fei Ge; Hou-Bin Ju; De-Quan Yang; Jian Liu; Jian Wang; Jun Lu; Xin Li; Wei-Yi Zhang; Pei-Hong Liu; Jin-Ping Zhou (Archives of Virology, 2014)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

Geographical information system-based assessment of ecological security in Changbai Mountain region - Xing-chang Lu; Ji-quan Zhang; Xiao-zhen Li (Journal of Mountain Science, 2014)

Characteristics of root boron nutrition confer high boron efficiency in Brassica napus cultivars - Lu Yang; Quan Zhang; Jina Dou; Ling Li; Longfei Guo; Lei Shi; Fangsen Xu (Plant and Soil, 2013)

Association of IL-1 Receptor Antagonist Gene VNTR Polymorphism with Ischemic Stroke in the Chinese Uyghur Population - Yeqing Tong; Jinjun Han; Xuhua Guan; Zuxun Lu; Xiaoping Miao; Jianjun Ye; Shuang-yi Hou; Yanwei Zhang; Yijie Geng; Yang Li; Faxian Zhan; Jiafa Liu; et al. (Biochemical Genetics, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Value of a new post-procedural intravascular ultrasound score in predicting target vessel revascularization after coronary drug-eluting stents implantation - Kai Xu; Ya-ling Han; Quan-min Jing; Shou-li Wang; Ying-yan Ma; Xiao-zeng Wang; Geng Wang; Zu-lu Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Cardioprotection by Hepc1 in cTnTR141W transgenic mice - Li Zhang; Dan Lu; Wei Zhang; Xiongzhi Quan; Wei Dong; Yanfeng Xu; Lianfeng Zhang (Transgenic Research, 2012)

Upper ocean near-inertial response to 1998 Typhoon Faith in the South China Sea - Lu Sun; Quan’an Zheng; Tswen-Yung Tang; Wen-Ssn Chuang; Li Li; Jianyu Hu; Dongxiao Wang (Acta Oceanologica Sinica, 2012)

Identification of neutral alleles at pollen sterility gene loci of cultivated rice (Oryza sativa L.) from wild rice (O. rufipogon Griff.) - Jin Quan Li; Muhammud Qasim Shahid; Jiu Huan Feng; Xiang Dong Liu; Xing Juan Zhao; Yong Gen Lu (Plant Systematics and Evolution, 2012)

Identification and molecular typing of Streptococcus agalactiae isolated from pond-cultured tilapia in China - Xing Ye; Jiong Li; Maixin Lu; Guocheng Deng; Xiaoyan Jiang; Yuanyuan Tian; Yingchun Quan; Qian Jian (Fisheries Science, 2011)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Molecular Cloning and Expression of cDNA Encoding the Cysteine Proteinase Inhibitor from Upland Cotton - Ming-feng Jiang; Sheng-wei Li; Min Chen; Ying-fan Cai; Yong-fang Xie; Biao Li; Quan Sun; Huai-zhong Jiang; Zheng Pan; Yun-ling Gao; You-Lu Yuan; Yu-zheng Shi (Journal of Plant Biology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of Low Molecular Weight Organic Anions on the Release of Arsenite and Arsenate from a Contaminated Soil - Shuzhen Zhang; Wei Li; Xiao-Quan Shan; Anxiang Lu; Peijiang Zhou (Water, Air, & Soil Pollution, 2005)

Characterization of HoMADS 1 and its induction by plant hormones during in vitro ovule development in Hyacinthus orientalis L. - Hong Xu; Xing Li; Quan Li; Shu Bai; Wen Lu; Xian Zhang (Plant Molecular Biology, 2004)

Isolation of HAG1 and its regulation by plant hormones during in vitro floral organogenesis in Hyacinthus orientalis L. - Quan Li; Xing Li; Shu Bai; Wen Lu; Xian Zhang (Planta, 2002)